CI-988 inhibits EGFR transactivation and proliferation caused by addition of CCK/Gastrin to lung cancer cells - Moody, Terry W. (J Mol Neurosci, 2015)
Cholecystokinin (CCK) receptors are G-protein coupled receptors (GPCR) which are present on lung cancer cells. CCK-8 stimulates the proliferation of lung cancer cells, whereas the CCK2R receptor antagonist CI-988 inhibits proliferation. GPCR for some gastrointestinal hormones/neurotransmitters mediate lung cancer growth by causing epidermal growth factor (EGF)R transactivation. Here, the role of CCK/gastrin and CI-988 on EGFR transactivation and lung cancer proliferation were investigated. Addition of CCK-8 or gastrin-17 (100 nM) to NCI-H727 human lung cancer cells increased EGFR Tyr(1068) phosphorylation after 2 min. The ability of CCK-8 to cause EGFR tyrosine phosphorylation was blocked by CI-988, gefitinib (EGFR tyrosine kinase inhibitor), PP2 (Src inhibitor), GM6001 (matrix metalloprotease inhibitor) and tiron (superoxide scavenger). CCK-8 nonsulfated and gastrin-17 caused EGFR transactivation and bound with high affinity to NCI-H727 cells, suggesting that the CCK2R is present. CI-988 inhibited the ability of CCK-8 to cause ERK phosphorylation and elevate cytosolic Ca(2+). CI-988 or gefitinib inhibited the basal growth of NCI-H727 cells or that stimulated by CCK-8. The results indicate that CCK/gastrin may increase lung cancer proliferation in an EGFR-dependent manner.